ACK family tyrosine kinase activity is a component of Dcdc42 signaling during dorsal closure in Drosophila melanogaster. - Sem, K.P.; Zahedi, B.; Tan, I.; Deak, M.; Lim, L.; Harden, N. (Molecular and Cellular Biology, 2002)
We have characterized Drosophila melanogaster ACK (DACK), one of two members of the ACK family of nonreceptor tyrosine kinases in Drosophila. The ACKs are likely effectors for the small GTPase Cdc42, but signaling by these proteins remains poorly defined. ACK family tyrosine kinase activity functions downstream of Drosophila Cdc42 during dorsal closure of the embryo, as overexpression of DACK can rescue the dorsal closure defects caused by dominant-negative Dcdc42. Similar to known participants in dorsal closure, DACK is enriched in the leading edge cells of the advancing epidermis, but it does not signal through activation of the Jun amino-terminal kinase cascade operating in these cells. Transcription of DACK is responsive to changes in Dcdc42 signaling specifically at the leading edge and in the amnioserosa, two tissues involved in dorsal closure. Unlike other members of the ACK family, DACK does not contain a conserved Cdc42-binding motif, and transcriptional regulation may be one route by which Dcdc42 can affect DACK function. Expression of wild-type and kinase-dead DACK transgenes in embryos, and in the developing wing and eye, reveals that ACK family tyrosine kinase activity is involved in a range of developmental events similar to that of Dcdc42.